PENGARUH PERENDAMAN LARUTAN ASAM CUKA TERHADAP KADAR LOGAM BERAT CADMIUM PADA KERANG HIJAU - Mifbakhuddin -; Rahayu Astuti; Agus Awaludin (JURNAL KESEHATAN, 2010)
BACKGROUND. The green shellfish (Perna viridis) was one of the shel(ish kind that was enjoyed by the community, had the economical value and the content of the nutrient taht really was good for consumed, when this green shellfish was dirtiest heavy Cd metal then will endanger for the health of the human body.OBJECTIVE. knew the influence of the submersion of the solution to acetic acid on the level of heavy metal cadmium to the green shelffish (Perna viridis)METHOD. The research true eksperiment with the plan that was used by Randommized Control Group Postest Design. The sample of the research was 24 green shellfish taht contained heavy Cd metal afterwards was soaked by using the solution to acetic acid respectively the concentration, where as the control was teh green shellfish that was not done by the submersion. The analysis ofthe data used One Way Anova.RESULT. In general the level of heavy cd metal in the control (without the treatment) was 77, 73 pg/lt, where as in general the level of heavy Cd metal in various concentration of the solution to acetic acid 10%, 15%, 20%, 25oZ that is 53,70 pg/lt, j1,00 pg/lt, 22,05 pg/lt, and 8,07 pg/lt. Therewas the influence of the submersion with the solution to acetic acid |ok, l0%, 15%, 20%, and 25%o against the level of heavy Cd metal to the green shelffish.CONCLUSION. The was the in/luence that was signiJicant against the level of heatty Cd metal with the submersion of the solution to acetic acid 10%, l5%, 20%, and 25%.KEYWORDS. The green shellfish, the solution to acetic acid, the level of heavy Cd metal.